Blood/plasma secretome and microvesicles - Inal, J.M.; Kosgodage, U.; Azam, S.; Stratton, D.; Antwi-Baffour, S.; Lange, S. (Biochimica et Biophysica Acta - Proteins and Proteomics, 2013)
A major but hitherto overseen component of the blood/plasma secretome is that of extracellular vesicles (EVs) which are shed from all blood cell types. These EVs are made up of microvesicles (MVs) and exosomes. MVs, 100 nm-1 μm in diameter, are released from the cell surface, and are a rich source of non-conventionally secreted proteins lacking a conventional signal peptide, and thus not secreted by the classical secretory pathways. Exosomes are smaller vesicles (≤ 100 nm) having an endocytic origin and released upon multivesicular body fusion with the plasma membrane. Both vesicle types play major roles in intercellular cross talk and constitute an important component of the secretome especially in the area of biomarkers for cancer. The release of EVs, which are found in all the bodily fluids, is enhanced in cancer and a major focus of cancer proteomics is therefore targeted at EVs. The blood/plasma secretome is also a source of EVs, potentially diagnostic of infectious disease, whether from EVs released from infected cells or from the pathogens themselves. Despite the great excitement in this field, as is stated here and in other parts of this Special issue entitled: An Updated Secretome, much of the EV research, whether proteomic or functional in nature, urgently needs standardisation both in terms of nomenclature and isolation protocols. This article is part of a Special Issue entitled: An Updated Secretome. © 2013 Elsevier B.V. All rights reserved.
Keywords: Blood/plasma; Exosome; Microvesicle; Secretome